Procedimiento para diseño de cimentaciones de equipos rotatorios - Vega Avendaño, Ricardo Leopoldo (My University, 2013)
cimentaciones, dinámico, vibraciones, procedimiento, recomendaciones, equipos, energía, generador, balanceo, rotatorio, resonancia, turbina, condensador, desalineación, tolerancia, masivo, concreto, calor, hidratación, centrífugo, suelo, estratificado
Keywords: cimentaciones, dinámico, vibraciones, procedimiento, recomendaciones, equipos, energía, generador, balanceo, rotatorio, resonancia, turbina, condensador, desalineación, tolerancia, masivo, concreto, calor, hidratación, centrífugo, suelo, estratificado